CFD simulation of free surface flow and heat transfer of liquid slag on a spinning disc for a novel dry slag granulation process. (27th September 2010) - Pan, Yuhua; Witt, Peter J.; Xie, Dongsheng
Molten slag is atomised by a spinning disc into droplets that are quenched via cold air to produce glassy slag granules. Steady-state two-dimensional CFD simulations of the multiphase flow and heat transfer in the slag and air were carried out. Also considered in the CFD model is conjugate heat transfer between liquid slag, solidified slag and the disc. The thickness and temperature of the slag film prior to its rupture were predicted. Influence of factors including the slag pouring rate, temperature and the disc spinning speed on the slag film thickness and temperature were investigated.